Detection of the LMC-induced sloshing of the Galactic halo. Issue 2 (1st July 2021) - Erkal, Denis; Deason, Alis J; Belokurov, Vasily; Xue, Xiang-Xiang; Koposov, Sergey E; Bird, Sarah A; Liu, Chao; Simion, Iulia T; Yang, Chengqun; Zhang, Lan; Zhao, Gang
ABSTRACT: A wealth of recent studies have shown that the LMC is likely massive, with a halo mass >10 11  M⊙ . One consequence of having such a nearby and massive neighbour is that the inner Milky Way is expected to be accelerated with respect to our Galaxy's outskirts (beyond ∼30 kpc). In this work, we compile a sample of ∼500 stars with radial velocities in the distant stellar halo, r GC  > 50 kpc, to test this hypothesis. These stars span a large fraction of the sky and thus give a global view of the stellar halo. We find that stars in the Southern hemisphere are on average blueshifted, while stars in the North are redshifted, consistent with the expected, mostly downwards acceleration of the inner halo due to the LMC. We compare these results with simulations and find the signal is consistent with the infall of a 1.5 × 10 11  M⊙ LMC. We cross-match our stellar sample with Gaia DR2 and find that the mean proper motions are not yet precise enough to discern the LMC's effect. Our results show that the Milky Way is significantly out of equilibrium and that the LMC has a substantial effect on our Galaxy.